Economic indicators for South and Central Asia input output tables. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication presents data visualization of economic statistics relevant for cross border production arrangements analysis, focusing on Bangladesh, Bhutan, India, Kazakhstan, the Kyrgyz Republic, Maldives, Nepal, Pakistan, and Sri Lanka. This was computed from ADB multi regional input output database which serves the increasing demand for structured, relevant, timely, and accurate data, especially with the onset of various economic research projects on global value chains. Supply and use tables and input output tables in the publication address the emerging need for more systematic and comprehensive approaches in data management, economic analysis, and policy research for national economies around the world.
Keywords: Economic indicators -- Econometric models; Economic indicators -- South Asia; Economic indicators -- Central Asia; Development economics; Electronic books